The proliferative and anti-apoptosis functions of KGF/KGFR contributes to bronchial epithelial repair in asthma - Wang, Jiongbo; Sun, Hongju; Liu, Yunshun (Pulmonary pharmacology & therapeutics, 2020)
This study aimed to investigate the effect of keratinocyte growth factor (KGF) on the apoptosis, proliferation, damage repair, intercellular adhesion, and inflammatory cytokine release of cultured 16HBE 14o-bronchial ECs in vitro. Bronchial epithelial cells (ECs) from all subjects were obtained by bronchoscopic brushing. The expression levels of KGF and its receptor KGFR in collected cells were determined using RT-qPCR and Western blotting. The apoptosis and adhesion molecules expression by KGF administration were determined using flow cytometry and Western blotting. This occurred when 16HBE 14o-cell lines cultured and were exposed to interferon-γ (IFN-γ) and tumor necrosis factor-alpha (TNF-α) in vitro. The role of KGF on proliferation and damage repair were analyzed using CCK-8, EdU and wound closure assays after 16HBE 14o-cells were scraped. The effect of KGF on the release of inflammation related cytokines by damaged ECs was measured using ELISA kits. Compared with healthy controls, the KGF and KGFR expression and apoptosis significantly increased in collected cells from asthma patients. In vitro, treatment of KGF may limit IFN-γ and TNF-α induced apoptosis by inhibiting apoptosis-associated markers in the TNF signaling pathway. Besides, KGF could limit the release of TSLP, IL-25 and IL-33 by damaged 16HBE 14o-cells. On the contrary, KGF could promote the intercellular adhesion and wound closure of cultured 16HBE 14o-cells via the increased expression level of intercellular junction proteins ICAM-1, β-catenin, E-cad, and Dsc3. In conclusion, KGF and KGFR may help bronchial ECs repair in asthma via the inhibition apoptosis of ECs while the promotion of proliferation and migration of ECs.